A new perspective on protecting the blood-retinal barrier against injury in diabetic retinopathy: mitophagy - Li, Mengtian; Yang, Liyang; Zhai, Haoyu; Qiao, Liping; Wang, Zhaobo; An, Xuedong; Wang, Jia (Frontiers in Endocrinology, 2025)
The blood-retinal barrier (BRB) comprises the inner blood-retinal barrier (iBRB) and the outer blood-retinal barrier (oBRB). The integrity of the BRB is essential to maintaining stability of the retinal microenvironment. Mitophagy plays a crucial role in maintaining organellar integrity by regulating mitochondrial quality and quantity. High glucose-induced mitophagy dysfunction contributes to diabetic retinopathy (DR) by damaging the BRB. This review presents mitophagy mechanisms under physiological conditions and examines changes across different cell types under DR-related pathological conditions that damage the BRB. It also summarizes drugs and targets that regulate mitophagy to stabilize the BRB and alleviate DR, offering new therapeutic insights.